PERAN IBU MEMBENTUK KELUARGA ISLAMI YANG BERDISIPLIN - Nora Zulfianti (Kafa`ah: Journal of Gender Studies, 2011)
The purpose of this article shows the role of a woman when having her function and her role as a mother when she get married and has children. This article focuses on describing how mother can be a teacher and a guideto create an Islamic family with good quality discipline. Mother plays her role maximally in structuring her family will appear the best family. Keywords : Role as a mother and familyCopyright © 2011 by Kafa`ah All right reservedDOI : 10.15548/jk.v1i2.81